Using PCM to improve building's thermal performance - Silva, Sandra Monteiro (2013)
Due to EU and worldwide high energy consumption of the buildings stock, it is important to take measures to reduce these needs and, consequently, reduce the EU energy dependency as well as the greenhouse gas emissions. To improve the behaviour of the buildings, concerning thermal comfort of the occupants and energy performance, it is necessary to reduce the thermal amplitudes, the winter heat losses, the summer heat gains and to store the energy from solar gains. The thermal insulation and the thermal inertia play an important role in this. The use of phase change materials (PCM) is a way of achieving thermal mass without increasing the weight of the buildings and simultaneously improving the thermal comfort conditions inside buildings, by increasing thermal energy storage. The good thermal characteristics of PCM can be used, in new and existing residential or office buildings, as a passive way of saving energy and reducing running costs for both heating and cooling seasons. Therefore it is possible to achieve an adequate behaviour of buildings reducing the energy needs, using solar gains, night cooling and off-peak electricity and, at the same time, increasing the comfort conditions inside the buildings, reducing temperature fluctuations and peak temperatures. In the Mediterranean Countries the selection of the type and amount of PCM to be used is a challenge due to the different characteristics needed to achieve an adequate behaviour of the buildings during winter and summer periods. In this study, the use of micro and macro-encapsulated PCM in buildings was studied to evaluate the annual behaviour and to identify the amount of PCM needed to ensure a suitable thermal and energy performance of the buildings.